Talking through procedures: An intelligent Space Station procedure assistant - Aist, Gregory; Dowding, John; Hockey, Beth Ann; Rayner, Manny; Hieronymus, James; Bohus, Dan; Boven, B.; Blaylock, Nate; Campana, Ellen; Early, Susana; Gorrell, Genevieve; Phan, Steven (EACL '03 Proceedings of the tenth conference on European chapter of the Association for Computational Linguistics, 2003)
We present a prototype system aimed at providing spoken dialogue support for complex procedures aboard the International Space Station. The system allows navigation one line at a time or in larger steps. Other user functions include issuing spoken corrections, requesting images and diagrams, recording voice notes and spoken alarms, and controlling audio volume.